Intermittent warming in 'BR-6' peaches cold stored - Kluge, Ricardo Alfredo; Hoffmann, Alexandre; Nachtigal, Jair Costa; Bilhalva, Aldonir Barreira; Fachinello, José Carlos (Pesquisa Agropecuaria Brasileira, 1996)
The objective of this paper was to verify the behavior of peaches cultivar BR-6 in cold storage and submitted to intermittent warming. The fruits were stored for 24 days at 0°C and 90-95% RH. The treatments were warmed after ten days in cold storage for 7, 21, 25 and 45 hs at 25-26°C and continuous storage at 0°C. The weigth loss of fruits was higher with longer exposure to intermittent warming. There was no influence of treatments on total soluble solids (TSS), total titratable acidity (TTA) and TSS/TTA. Pulp firmness decreased markedly in fruits after intermittent warming. Decay was higher in fruits warmed for 45 hs. The intermittent warming for 21, 25 and 45 hs reduced markedly pulp internal browning in fruits.